Student Quality-of-Life in Academic Culture Perspective - Sugara, Gian Sugiana (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2018)
Quality of life is a study of human happiness, strength and life satisfaction for the better life. Quality of life as an important aspect in the development and lives of individuals known to correlate with various factors, but have not revealed many factors related to culture, especially in Indonesia. This study aims to reveal the quality of life on students of Guidance and Counseling Study Programme FKIP Universitas Muhammadiyah Tasikmalaya. The study was conducted on 151 students consisting of 48 men and 113 women. The average age of study participants was 19-21 years old. The instrument used is the Quality-of-Life Inventory. Descriptive statistical data analysis used in this study. Results of the study showed significant difference in the quality of life between students female and male. Quality of life male student higher than female student. Quality of life Sundanese cultural background of students is the higher than Javanese students. Student culture perspective on quality of life related to balance the academic need, organization oriented and personal need.